CATALYSTS: MECHANISMS, TYPES, AND THEIR INDUSTRIAL APPLICATIONS - Qurbonova Manzura Fardayevna (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract: Catalysts are substances that accelerate chemical reactions without being consumed in the process. They are fundamental in modern chemical industry, environmental protection, and biological systems. This paper discusses the classification of catalysts, their mechanisms of action, and their industrial significance. Additionally, recent advances in nanocatalysis and sustainable catalytic systems are reviewed.